The 'Curious Effects' of Acting: Homosexuality, Theatre and Female Impersonation at the University of Cambridge, 1900–39. (10th November 2021) - Janes, Dominic
Abstract: The University of Cambridge educated a significant proportion of Britain's elite in the early twentieth century. The homosocial environment of the colleges was similar in many ways to that of the single-sex public boarding schools which many of the undergraduates had attended. Student theatre was a popular activity, and because such shows were acted by single-sex ensembles, there was a strong tradition of female impersonation on stage. The interwar diaries of Cecil Beaton, who identified privately as a homosexual man, provide an unusually detailed source of information about a period when sexual controversy began to surround theatrical cross-dressing. In the 1930s, when moves were made to open previously men-only university drama clubs to women, the issue of male homosexuality and its alleged connections with student theatre came to be widely discussed. This reflected significant changes in the ways in which queerness was accommodated within the predominantly male environment of the University.